Phase II study of acalabrutinib in ibrutinib-intolerant patients with relapsed/refractory chronic lymphocytic leukemia - Kerry A. Rogers; Philip A. Thompson; John N. Allan; Morton Coleman; Jeff P. Sharman; Bruce D. Cheson; Daniel Jones; Raquel Izumi; Melanie M. Frigault; Cheng Quah; Rakesh K. Raman; Priti Patel; et al. (Haematologica, 2021)
B-cell receptor signalling inhibition by targeting Bruton tyrosine kinase (BTK) is effective in treating chronic lymphocytic leukemia (CLL). The BTK inhibitor ibrutinib may be intolerable for some patients. Acalabrutinib is a more selective BTK inhibitor that may be better tolerated by patients who are intolerant to ibrutinib. A phase 2 study of acalabrutinib was conducted in patients with relapsed/refractory CLL who were ibrutinib-intolerant and had continued disease activity. Intolerance was defined as having discontinued ibrutinib due to persistent grade 3/4 adverse events (AEs) or persistent/recurrent grade 2 AEs despite dose modification/interruption. Patients received oral acalabrutinib 100 mg twice daily until disease progression or intolerance. Sixty patients were treated. Overall response rate to acalabrutinib was 73% and three patients (5%) achieved complete remission. At median follow-up of 35 months, the median progressionfree and overall survival were not reached; 24-month estimates were 72% and 81%, respectively. The most frequent AEs with acalabrutinib were diarrhea (53%), headache (42%), contusion (40%), dizziness (33%), upper respiratory tract infection (33%), and cough (30%). Most common reasons for acalabrutinib discontinuation were progressive disease (23%) and AEs (17%). Most patients with baseline samples (49/52; 94%) and all with on-treatment samples (3/3; 100%) had no detectable BTK and/or PLCG2 mutations. Acalabrutinib is effective and tolerable in most patients with relapsed/refractory CLL who are intolerant of ibrutinib. Acalabrutinib may be useful for patients who may benefit from BTK inhibitor therapy but are ibrutinib intolerant.